Combined targeting of pathways regulating synaptic formation and autophagy attenuates Alzheimer’s disease pathology in mice - Bjorkli, Christiana; Hemler, Mary; Julian, Joshua B.; Sandvig, Axel; Sandvig, Ioanna (Frontiers in Pharmacology, 2022)
All disease-targeting drug trials completed to date have fallen short of meeting the clinical endpoint of significantly slowing cognitive decline in Alzheimer’s disease (AD) patients. In this study, we repurposed two FDA-approved drugs, Fasudil and Lonafarnib, targeting the Wnt signaling and endosomal-lysosomal pathways respectively, to test their potential to attenuate AD pathology in 3xTg AD mice. Using intracerebral microdialysis, we simultaneously infused these disease-targeting drugs separately and in combination, while collecting cerebrospinal fluid (CSF). We found that Fasudil reduced intracellular amyloid-β in young, and amyloid plaques in old animals, and overall CSF amyloid-β. Lonafarnib reduced tau neuropathology and CSF tau biomarkers in young and old animals. Co-infusion of both drugs was more effective in reducing intracellular amyloid-β than either drug alone, and appeared to improve contextual memory performance. Taken together, these findings lend support to the application of repurposed drugs to attenuate AD neuropathology at various therapeutic time windows.